Crystal structure of the C-terminal domain of tubulin-binding cofactor C from Leishmania major - Barrack, Keri L. (Mol Biochem Parasitol, 2015)
Tubulin-binding cofactor C stimulates GTPase activity and contributes to the release of the heterodimeric α/β-tubulin from a super-complex of tubulin monomers and two ancillary cofactors. We have determined the 2.2 Å resolution crystal structure of the C-terminal domain of tubulin-binding cofactor C from Leishmania major based on single wavelength anomalous dispersion measurements targeting a selenomethionine derivative. Although previously predicted to consist of two domains the structure is best described as a single domain dominated by a right-handed β-helix of five turns that form a triangular prism. One face of the prism is covered by the C-terminal residues leaving another face solvent exposed. Comparisons with an orthologous human GTPase activating protein match key residues involved in binding nucleotide and identify the face of the β-helix fold likely involved in interacting with the β-tubulin:GTP complex.